Strength of Backfilling : In Situ Test Methods and Numerical Modeling - Keshvary, Rafi (2013)
In very shallow dipping ore bodies or where the ore is wide Boliden sometimes use drift and fill mining. In order not to create too large spans rooms are backfilled with cement stabilized hydraulic fill before excavating the adjacent room. The purpose of the fill is to support the walls and roof. The strength of fill is mainly governed by the amount of cement in it. The amount should be enough to keep the wall remains vertical when the adjacent room is excavated.Boliden operates the Garpenberg mine which comprises of different orebodies where Lappberget orebody is one that has advanced to the depth of 1250 m. Transverse sub-level stoping has been the mining method used at the Lappberget mine since the depth of 1100 m. This mining method requires backfilling in which pastefill is used. The background of this thesis work was the demand from Boliden to get a new test method which could be used to measure the in-situ strength of the pastefill in the mine. As a first part of the work, a test method was selected in the category of the penetration resistance methods called Basic Force Gauge (BFG). The method should pass three testing phases in order to ensure its applicability. First theoretical studies were performed in order to determine the required penetration force considering the strength of the pastefill. Second, laboratory tests were performed to check the accurate function of the BFG and precision of the results then calibration of the BFG. For this task eight different pastefill recipes were casted in the Luleå University’s Complab for trying BFG as well as performing uniaxial compressive strength (UCS) tests. The results of the penetration force and UCS were calibrated in order to establish a method to estimate strength of the pastefill. Third, the BFG were used in the Garpenberg mine on the deposited pastefill to check the real function of the equipment and to estimate a relevant pastefill’s strength. As a second part of the work, 12 mining sections for the transverse sub-level stoping at the Lappberget ...